Analisis Perencanaan Sumber Daya Manusia dan Dampaknya Terhadap Motivasi Kerja Pegawai di Kantor Camat Lolofitu Moi - laoli, Eka putri nanjaya; Zega, Yamolala; Waruwu, Eliyunus; Bate'e, Maria Magdalena (Eqien - Jurnal Ekonomi dan Bisnis, 2025)
This research aims to analyze human resource (HR) planning and its impact on employee work motivation at the Lolofitu Moi Subdistrict Office, West Nias Regency. The background to this research is based on the importance of HR planning in achieving organizational goals and increasing employee work motivation. Good work motivation is expected to increase employee performance and productivity. The research method used is a qualitative approach with descriptive research type. Primary data was obtained through in-depth interviews with eight employees at the Lolofitu Moi Subdistrict Office, including the Subdistrict Head and the Subdistrict Secretary. Secondary data was obtained from official documents and relevant reports. The research results show that HR planning at the Lolofitu Moi Subdistrict Office includes the recruitment process, developing employee skills and knowledge, as well as a compensation system that is adjusted to government regulations. However, there are challenges such as the unavailability of supporting facilities such as WiFi which has a negative impact on work efficiency. Apart from that, less than optimal implementation of employees' main duties and functions (tupoksi) results in low work motivation. This research concludes that effective HR planning can increase employee work motivation, but there is a need to improve infrastructure and evaluate employee placement to suit their skills and potential. Recommendations given include improving technological facilities in the office and adjusting employee placement based on job analysis to create a productive work environment.